Cholangiocellular carcinoma in a cat - M. Kemal Çiftçi; Mustafa Ortatatlı; Sırrı Avki (Eurasian Journal of Veterinary Sciences)
In this case report, a cholangiocellular carcinoma diagnosed in a 13 years-otd female cat was described. The cat, euthanasied intraoperatively, was necropsied, and grossly, grayish coloured, rounded or cauliflower shaped multinodular masses sized 8-9 centimetres were observed in the liver. The same nodules were confirmed in the lungs, also. Microscopic examinations of the liver and lungs revealed that tumoral masses were originated from intrahepatic bile duct epithelial cells that orientated as commonly wide radial or rarely asinar manner. The case was classified as a cholangiocellular carcinoma.